Thrypticus atomus Frey 1915 - Negrobov, Oleg P.; Naglis, Stefan (Zenodo, 2020)
atomus Frey Thrypticus atomus Frey, 1915: 47. Distribution. Austria, Belgium, Czech Republic, Finland, Hungary, Latvia, Netherlands, Russia (European part, Leningrad region, Siberia, Yakutia), Sweden. : Published as part of Negrobov, Oleg P. & Naglis, Stefan, 2020, Two new species of Thrypticus Gerstäcker from Turkey (Diptera, Dolichopodidae) with checklist and key to Palaearctic species, pp. 111-125 in Zootaxa 4858 (1) on page 118, DOI: 10.11646/zootaxa.4858.1.8, http://zenodo.org/record/4411639 : {"references": ["Frey, R. (1915) Zur Kenntnis der Dipterenfauna Finlands III, Dolichopodidae. Acta Societas pro Fauna et Flora Fennica, 40 (5), 1 - 80."]}